2014
DOI: 10.1177/0011128714530824
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Citizenship Evidence-Based Probation Supervision Program Using a Stepped Wedge Cluster Randomized Controlled Trial

Abstract: This study evaluated a Risk-Need-Responsivity (RNR) evidence-based offender supervision program, Citizenship, using a randomized controlled trial (RCT). Citizenship has a cognitive-behavioral basis and focuses on education, increasing motivation to change, and community integration. The RCT is a stepped wedge cluster randomized design that has rarely been used in criminal justice and overcomes some ethical objections to RCT implementation. Participants were all medium-and high-risk offenders commencing probati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…For example, Lowenkamp et al (2014) found that Staff Training Aimed at Reducing Rearrest (STARR) was associated with a reduction in recidivism for moderate risk offenders, but that there was no effect for high risk offenders unless STARR related skills were employed alongside Motivational Interviewing techniques. Pearson et al (2016) found a non-significant effect of the ‘Citizenship’ programme across all the offenders sampled, but a statistically significant reduction in reoffending amongst high risk offenders. These differential findings associated with risk level in some studies therefore suggest a more nuanced understanding of effect sizes (the effectiveness of the intervention for different groups) than overall effect sizes suggest.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…For example, Lowenkamp et al (2014) found that Staff Training Aimed at Reducing Rearrest (STARR) was associated with a reduction in recidivism for moderate risk offenders, but that there was no effect for high risk offenders unless STARR related skills were employed alongside Motivational Interviewing techniques. Pearson et al (2016) found a non-significant effect of the ‘Citizenship’ programme across all the offenders sampled, but a statistically significant reduction in reoffending amongst high risk offenders. These differential findings associated with risk level in some studies therefore suggest a more nuanced understanding of effect sizes (the effectiveness of the intervention for different groups) than overall effect sizes suggest.…”
Section: Resultsmentioning
confidence: 79%
“…For example, A US-based programme (Proactive Community Supervision; Taxman, 2008) found a statistically significant effect; that offenders who undertook the programme were less likely to be rearrested (32%) than those who did not (42%). In a UK context, Pearson et al (2011) and Pearson et al (2016) investigated ‘Citizenship’, a structured probation programme based on ‘What Works’ principles. Findings from both studies suggest that the programme was associated with reductions in recidivism for the participating offenders, although in the 2016 study the overall effect for all risk levels was not significant (this finding possibly being a consequence of the more rigorous randomised research design used).…”
Section: Resultsmentioning
confidence: 99%
“…In general terms, results are somewhat mixed, and may depend on both the intensity of treatment as well as the quality of the instructors. For instance, Pearson et al (2016) conduct a randomized control trial to test the effectiveness of a program (known as "Citizenship") in the United Kingdom that has a cognitive behavioral basis and focuses on education, promoting motivation to change, and community integration. They find that the program reduces convictions for high-risk probationers.…”
Section: Rehabilitationmentioning
confidence: 99%
“…As of April 8, 2014, our search yielded 10 studies that were eligible for inclusion. One recent validation of a training program (Pearson, McDougall, kanaan, Torgerson, & Bowles, 2014) based on evidence-based principles was not included due to complexities in the methodology. The study utilized a hierarchical step-wedge cluster to examine the impact of officer training on client outcome among a large sample of probationers.…”
Section: Search Strategymentioning
confidence: 99%